2013
DOI: 10.1093/carcin/bgt162
|View full text |Cite
|
Sign up to set email alerts
|

(S)-N'-Nitrosonornicotine, a constituent of smokeless tobacco, is a powerful oral cavity carcinogen in rats

Abstract: Currently, smokeless tobacco products are being proposed as an alternative mode of tobacco use associated with less harm. All of these products contain the tobacco-specific carcinogen N'-nitrosonornicotine (NNN). The major form of NNN in tobacco products is (S)-NNN, shown in this study to induce a total of 89 benign and malignant oral cavity tumors in a group of 20 male F-344 rats treated chronically with 14 p.p.m. in the drinking water. The opposite enantiomer (R)-NNN was weakly active, but synergistically en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 35 publications
7
95
0
Order By: Relevance
“…5 Balbo et al reported a significant association between NNN in drinking water and the development of oesophageal and oral cancers in rats. 27 In addition, NNK has been found to increase the risk of lung cancer. 28 The NNN and NNK compounds are also known to form haemoglobin adducts in humans as well as in experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…5 Balbo et al reported a significant association between NNN in drinking water and the development of oesophageal and oral cancers in rats. 27 In addition, NNK has been found to increase the risk of lung cancer. 28 The NNN and NNK compounds are also known to form haemoglobin adducts in humans as well as in experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely, although not definitively demonstrated, due to direct contact with esophageal mucosa during swallowing. Interestingly, Balbo et al investigated the carcinogenic effects of NNN enantiomers, (S)-NNN and (R)-NNN, in rats [33]. Rats were administered either (S)-NNN, (R)-NNN, racemic NNN, or tap water (control group) in their drinking water.…”
Section: Tobacco Carcinogensmentioning
confidence: 99%
“…Interestingly, tumor development in rats receiving racemic NNN in the oral cavity and esophagus was significantly greater than that in the (S)-NNN only group and greater than the added effects of (S)-NNN and (R)-NNN. This suggests that (R)-NNN acts as a co-carcinogen, synergistically enhancing the effects of (S)-NNN while itself being relatively inactive in terms of tumorgenecity [33]. This data is clinically relevant because (S)-NNN is the predominant form of NNN present in smokeless tobacco and is found at higher levels than combustible tobacco.…”
Section: Tobacco Carcinogensmentioning
confidence: 99%
“…Alternatively, the proliferating cell layer could be dissected out for adduct analysis (e.g., by laser capture microdissection), but the amount of DNA would be insuffi cient for analysis by mass spectrometry given the sensitivity of the technique currently. Conceivably, cell types of interest could be separated in bulk using cell-sorting techniques (e.g., [ 43 ]). However, this would require amounts of tissue that could not be obtained from humans.…”
Section: Anatomical Considerationsmentioning
confidence: 99%